Host-microbe interactions - San Francisco, Michael; San Francisco, Brian (Progress in molecular biology and translational science, 2016)
Host-Microbe Interactions, the latest volume in the Progress in Molecular Biology series, provides a forum for the discussion of new discoveries, approaches, and ideas in molecular biology. It contains contributions from leaders in their respective fields, along with abundant references. This volume is dedicated to the subject of host-microbe interactions. Provides the latest research on host-microbe interactions, including new discoveries, approaches, and ideasContains contributions from leading authorities on topics relating to molecular biologyInforms and updates on all the latest developments in the field